2013
DOI: 10.1007/s00431-013-2241-y
|View full text |Cite
|
Sign up to set email alerts
|

Atypical antipsychotic poisoning in young children: a multicentre analysis of poisons centres data

Abstract: Although paediatric patients frequently suffer from intoxications with atypical antipsychotics, the number of studies in young children, which have assessed the effects of acute exposure to this class of drugs, is very limited. The aim of this study was to achieve a better characterization of the acute toxicity profile in young children of the atypical antipsychotics clozapine, olanzapine, quetiapine, and risperidone. We performed a multicentre retrospective analysis of cases with atypical antipsychotics intox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…The clinical profile of antipsychotic poisoning in our cases demonstrated that about half of the studied cases had mild general symptoms like tachycardia (46.67%), tachypnea (46.67%) and miosis (56.7%) while, small number were presented with serious manifestations like GCS less than 8 (8.3%) and dystonia (6.7%). This was in agreement with the previous reports of lower morbidity and lower lethal effect of antipsychotic poisoning in most of cases specially the atypical ones (Capel et al, 2000, Rasimas and Liebelt, 2012, Meli et al, 2014. Most of our cases didn't consume big doses and most of those who poisoned themselves intended only to seek attention not to kill themselves or ingested the drug accidentally.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The clinical profile of antipsychotic poisoning in our cases demonstrated that about half of the studied cases had mild general symptoms like tachycardia (46.67%), tachypnea (46.67%) and miosis (56.7%) while, small number were presented with serious manifestations like GCS less than 8 (8.3%) and dystonia (6.7%). This was in agreement with the previous reports of lower morbidity and lower lethal effect of antipsychotic poisoning in most of cases specially the atypical ones (Capel et al, 2000, Rasimas and Liebelt, 2012, Meli et al, 2014. Most of our cases didn't consume big doses and most of those who poisoned themselves intended only to seek attention not to kill themselves or ingested the drug accidentally.…”
Section: Discussionsupporting
confidence: 93%
“…The present study showed that pupil was constricted in more than half of cases (56.7%), dilated in 3.3% and normal in 40% of cases. Pupil size changes were recorded by some previous researches (Pickford, 2000, Meli et al, 2014. Miosis was explained by the α1 adrenergic receptor blocking effect of antipsychotics while mydriasis was explained by the anticholinergic effect of these drugs (Stahl, 2013).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Unlike our study which revealed a higher incidence of moderate and severe cases. Meanwhile, different literatures demonstrated occurrence of ECG changes in both typical and atypical antipsychotics overdose (Tan et al, 2009 andMeli et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…According to the current increase in antipsychotics prescription, the clinicians confront more cases of antipsychotics poisoning in clinical practice. Thus, predicting major outcomes in such poisoned patients is important to guide management priorities for better outcome (Meli et al, 2014 andBhandari et al, 2018). The standard 12-lead electrocardiogram (ECG) is an available, inexpensive and non-invasive bedside test (Isiguzo et al, 2017).…”
mentioning
confidence: 99%